Pengawasan bibliografi terhadap buku Islam terbitan Indonesia (Studi terhadap cantuman buku-buku Islam dalam BNI dan KDT tahun 2000-2005) - Siti Maryam (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2012)
This article discussed a result of quantitative analysis descriptive approach focused on conducting attitude of Islamic book publisher in Jakarta to the Legal Deposit (UU Rl. No. 4/1990) and the concept of bibliographic control and its correlation with the Islamic book entries in BNI (Bibliografi Nasional lndonesia=Indonesian National Bibliography) and KDT (Katalog Dalam Terbitan = Cataloging in Publication, held in 2007. The results of this research indicated that there is no correlation between the Islamic book publishers attitude's to the Legal Deposit with the Islamic book entries both in BNI and KDT, and the Islamic book publisher's attitude did not give a significant contribution to Islamic book entries both in the BNI and KDT. Kata kunci: pcngawasan bibliografi, buku Islam, Perpustakaan Nasional, Bibliografi Nasional Indonesia(BNI), Katalog Dalam Terbitan (KDT), sikap penerbit